Antibiotics and Antibiotic Resistance in Agroecosystems: State of the Science. Issue 2 (1st March 2016) - Williams‐Nguyen, Jessica; Sallach, J. Brett; Bartelt‐Hunt, Shannon; Boxall, Alistair B.; Durso, Lisa M.; McLain, Jean E.; Singer, Randall S.; Snow, Daniel D.; Zilles, Julie L.
Abstract : We propose a simple causal model depicting relationships involved in dissemination of antibiotics and antibiotic resistance in agroecosystems and potential effects on human health, functioning of natural ecosystems, and agricultural productivity. Available evidence for each causal link is briefly summarized, and key knowledge gaps are highlighted. A lack of quantitative estimates of human exposure to environmental bacteria, in general, and antibiotic‐resistant bacteria, specifically, is a significant data gap hindering the assessment of effects on human health. The contribution of horizontal gene transfer to resistance in the environment and conditions that might foster the horizontal transfer of antibiotic resistance genes into human pathogens also need further research. Existing research has focused heavily on human health effects, with relatively little known about the effects of antibiotics and antibiotic resistance on natural and agricultural ecosystems. The proposed causal model is used to elucidate gaps in knowledge that must be addressed by the research community and may provide a useful starting point for the design and analysis of future research efforts. Core Ideas: We propose a simple causal model of antibiotics and antibiotic resistance in agroecosystems. Lack of data on human exposure to resistance in the environment hinders risk assessment. The contribution of horizontal gene transfer to resistance in the environment requires research. Antibiotics in environment may mediate effect of antibiotic use on resistance in the environment. Effects of antibiotics and antibiotic resistance on natural and agricultural ecosystems are largely unknown.